Development of Early Childhood Student Agency in Efforts to Realize Free Play (Case Study of the Aksi Pasukan HEPI Program at TK Negeri Pembina Subang) - Fitria, Risa; Djoehaeni, Heny (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
The essence of independent Playing in the context of early childhood education is to provide meaningful play experiences so that they get the opportunity to explore their environment, solve problems, and become leaders in the learning process. One of the efforts to realize the freedom of play is to develop student agency in the child. Student agency is a child's competence to determine his learning process through expressing ideas and opinions, making choices, and making decisions to create a sense of ownership for what he does. This study aims to analyze the development of student agency which is packaged in a school program, namely the Aksi Pasukan HEPI at the TK Negeri Pembina, Subang Regency. The research method used is qualitative with a case study approach, with data collection being observation, interviews, and documentation. The result of the research is that the Aksi Pasukan HEPI program can develop early childhood student agency, by empowering all assets owned by the school and its environment.